Literatura e filosofia: as personagens conceituais do romance Júlia ou A Nova Heloísa de Jean-Jacques Rousseau na perspectiva de Gilles Deleuze e Félix Guattari - NUNES, Lidia Cristina Costa (2022)
This work aims to analyze the characters of the novel Júlia ou A nova Heloísa by Jean-Jacques Rousseau from the perspective of Gilles Deleuze and Félix Guattari. With this, we seek to answer the following problem: Why are the characters in the novel Júlia ou A nova Heloísa considered conceptual? The way to answer this question is in literature and philosophy for dealing with the novel genre and also for covering philosophical concepts of Deleuze, Guattari and Rousseau. Regarding its approach, the research is qualitative and of an imminently theoretical nature. The study consists of bibliographic analysis and emphasizes the investigation about the characters of the Rousseauian novel based on the following topics: Introduction, What is a Concept? The Plan of Immanence and The Conceptual Characters of the work What is Philosophy? by Gilles Deleuze and Félix Guattari. That said, the text is organized into three sections: the first addresses the historiography of western literature, relating it to the work of Jean-Jacques Rousseau, the second seeks to identify the characters of Rousseau's novel, clarifying the reasons why Gilles Deleuze and Félix Guattari consider the characters of the Júlia ou Nova Heloísa manuscript as conceptual, and, finally, the third section presents the concept of materialism of Rousseau's sage in the light of Gilles Deleuze.